A Curious Case of Pseudothrombocytopenia due to In Vitro Agglutination - Le Zhong; Juskaran Chadha; Ali Ameri (Case Reports in Hematology)
Pseudothrombocytopenia (PTCP) is a laboratory phenomenon that can occur in hospitalized patients, with approximately 0.1 to 0.2% due to ethylenediaminetetraacetic acid (ETDA). The EDTA-dependent mechanism of PTCP occurs due to a conformational change of platelet surface glycoprotein IIb/IIIa (GPIIb/IIIa) caused by EDTA, which allows natural IgM or IgG auto-antibodies to bind to GPIIb/IIIa, leading to platelet agglutination. In most cases, PTCP resolves when a repeat blood sample is drawn in collection tubes containing either citrate or heparin. Here, we report a case of a 23-year-old female presenting with symptoms of gastroenteritis. She exhibited PTCP with blood draws obtained in not only collection tubes containing ETDA, but also with collection tubes containing heparin and citrate, which is highly unusual. The lack of resolution of platelet clumping in collection tubes containing either heparin or citrate suggests that heparin or citrate may also cause conformational changes to platelet surface glycoproteins in a similar mechanism as that of EDTA that allows binding of certain auto-antibodies.